Additions of trastuzumab to preoperative chemotherapy or chemoimmunotherapy for patients with potentially resectable stage III to IVB HER2-positive gastric cancer - Zhang, Xuchen; Tian, Yulong; Wang, Huiyun; Song, Shanai; Chen, Yunqing; Liu, Ning; Zhang, Chuantao; Huang, Xiao; Jiang, Haitao; Hou, Helei (Frontiers in Immunology, 2025)
BackgroundWhether the addition of trastuzumab to chemo(immuno)therapy for the preoperative treatment of patients with potentially resectable HER2-positive gastric cancer has clinical benefits remains to be explored. This real-world observational study was designed to evaluate the efficacy and safety of trastuzumab plus chemo(immuno)therapy for neoadjuvant or conversion therapy in patients with potentially resectable HER2-positive gastric cancer.MethodsWe retrospectively collected the clinical data of treatment-naïve patients with potentially resectable stage III to IVB HER2-positive gastric cancer who received preoperative therapy prior to D2 gastrectomy. The main outcomes of interest included tumour regression grade (TRG), treatment-related adverse events (TRAEs), and event-free survival (EFS).ResultsA total of 40 patients were included in the analysis, specifically, 27 patients (67.5%, 95% CI 0.520-0.799) received preoperative trastuzumab plus chemo(immuno)therapy, and 13 patients (32.5%, 95% CI 0.201-0.480) received chemo(immuno)therapy. All these patients subsequently underwent D2 gastrectomy. Regarding surgical outcomes, TRG0/1 rates were 33.3% (95% CI 0.186-0.522) in the trastuzumab-containing treatment group and 15.4% (95% CI 0.043-0.422) in the chemotherapy/chemoimmunotherapy group. Regarding safety, 66.7% (95% CI 0.478-0.814) of patients in the trastuzumab-containing treatment group and 61.5% (95% CI 0.355-0.823) of patients in the chemotherapy/chemoimmunotherapy group experienced preoperative TRAEs. The probabilities of EFS were not statistically significant between the two groups by the last follow-up.ConclusionAdditions of trastuzumab to preoperative chemotherapy or chemoimmunotherapy resulted in a TRG0/1 rate of 33.3% among patients with potentially resectable HER2-positive gastric cancer, and the combined regimen exhibited a favourable safety profile.